2004
DOI: 10.2169/internalmedicine.43.415
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry for the Differentiation of Peritoneal Disseminated Carcinoma of Unknown Origin

Abstract: We report a woman with ascites, hydrothorax, pancreatic tumor, left cystic ovarian tumor, and an elevated serum cancer antigen 125 level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Finally, pitfalls may be observed when studying cancer antigens, such as CA19.9, CA125 and CA150, since these markers display extensive cross-reactions and related antibodies are known to react to several normal and neoplastic epithelial cells of different origins 136140…”
Section: Pitfalls In Results Interpretationmentioning
confidence: 99%
“…Finally, pitfalls may be observed when studying cancer antigens, such as CA19.9, CA125 and CA150, since these markers display extensive cross-reactions and related antibodies are known to react to several normal and neoplastic epithelial cells of different origins 136140…”
Section: Pitfalls In Results Interpretationmentioning
confidence: 99%
“…As ILC may present only as an asymmetric density rather than a dominant tumor mass [2], it could be missed on routine mammography evaluation. Histopathological and immunohistochemical analysis of biopsy specimen taken from GI metastatic sites are key in determining primary tumors [3]. Although GI metastases from ILC have been rare, the recognition of these entities is very important for making prompt diagnosis and providing appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation between these primaries is necessary for treatment options, prognosis, and response to the therapy. 2,3 It has been shown that patients with advanced ovarian cancer are more responsive to chemotherapy than those with pancreatic cancer. 4,5 There are no reliable cytomorphological features to differentiate metastatic carcinoma of pancreas from ovary in effusion cytology.…”
mentioning
confidence: 99%